SEMINAR PEMANFAATAN MICROSOFT FORMS SEBAGAI MEDIA PEMBUATAN UJI KOMPETENSI DIGITAL DAN EVALUASI PEMBELAJARAN SISWA MTS ISLAMIYAH WONGSOREJO - Zaehol Fatah; Intan Nayla Widad Hidayat (Jurnal Padamu Negeri, 2026)
Infrastructure Alongside the digital technology transformation in education, the demand for more interactive and efficient learning evaluation has driven the adoption of digital assessment and evaluation platforms. This seminar aims to enhance the understanding of MTS Islamiyah Wongsorejo students in optimizing the use of Microsoft Forms in digital learning and evaluation processes. The method used in this study is descriptive qualitative, encompassing seminars, simulations, and intensive mentoring, supported by pre-test and post-test as assessment instruments. Data collection techniques were carried out through observation, documentation, and practical test results. A significant improvement was observed in students' skills in operating Microsoft Forms, reflected in the increase of the average pre-test score of 63.5 to 86.8 on the post-test, equivalent to an improvement of 38.4%. Students were able to utilize the available features as well as instant feedback. This was further supported by intensive mentoring, which proved effective in identifying arising obstacles and building students' confidence in using technology. Therefore, a more adaptive and evaluative learning experience can be obtained by students through the use of Microsoft Forms as a learning medium. To support the transformation of technology-based learning, its implementation needs to be continuously developed to complement conventional learning.